Preemptive Analgesic Effect of Ibuprofen in 3rd Molar Impactions Surgery of Jaw - Ahmed Jawad Khan, Najeeb Ullah, Sadia Iqbal, Zakir, Shehzaib Ejaz, Kashaf ud Doja Tariq, (Pakistan Journal of Medical & Health Sciences, 2024)
Introduction: Ibuprofen is a propionic acid derivative that has analgesic, anti-inflammatory and antipyretic effects. It is well known that ibuprofen is effective in postoperative dental pain. It is more advantageous to use an analgesic agent pre-operative since this way prevents central sensitization of peripheral receptors which normally happens as a consequence of surgical trauma that intensifies postoperative pain. Materials and Methods: A total of 60 cases with chief complaint of pain and recurrent pericoronitis caused by the 3rd molar impaction in the ages of 17-35 years and both the sex were taken. The patients who had a history of hypersensitivity to NSAIDs and peptic ulcer were excluded. Group A consisted of 600mg of Ibuprofen (oral) 1 hour before the procedure and group B consisted of 600mg of Ibuprofen (oral) 1 hour after the procedure. All the patients were provided with standard after surgery care. The measure of outcome was postoperative pain. Results: The average age of group A patients was1: 26.53 years SD 4.64 and group B was 1: 27.53 years SD 4.71. Most of the patients 31 (51.67) were aged between 26 to 35 years. The sample size was 60 (41 (68.33) males and 19 (31.67) females) males to females ratio 2:1. Pre-emptive Group A (pre-emptive group) recorded a mean post-operative pain of 1.97:1.76 and post-operative Group B recorded a mean post-operative pain of 4.00:1.44 (p-value = 0.0001). Conclusion: The conclusion made by the current study has been that preemptive analgesic effect of ibuprofen is superior in 3 rd molar impaction surgery compared with post-operative group. Keywords: third molar surgery, preemptive ibuprofen, pain.